EU biofuel policies: Income effects and lobbying decisions in the German agricultural sector. (March 2016) - Deppermann, Andre; Offermann, Frank; Puttkammer, Judith; Grethe, Harald
Abstract: European Union (EU) policymakers have persistently supported first-generation biofuels despite the clearly emerging picture of small or even negative green house gas mitigation effects. This leads to the conclusion that support is driven by other objectives, for example income effects. Against this background, the main objective of this article is to analyse the income effects of abolishing biofuel policies, as well as to explore the link between these effects and lobbying decisions taken by farmers' associations representing different groups of German farmers. Income effects are estimated for different farm types and regions, and differences between farm net value added and family farm income are analysed. To understand the link between income effects and lobbying decisions, our quantitative results are compared with the biofuel policy positions of different farmers' associations. Our results suggest that, in the long run, average income effects are small, especially if the ownership of production factors is accounted for in the income calculation. Many farms show losses if biofuel support is abolished, but others even benefit from lower rental costs and experience positive income effects. Farmers' associations seem to be able to well assess the income effects of EU biofuel policy for different types of farms. Highlights: We model disaggregate effects of abolishing EU biofuel policies on German farms. We find negative but small impacts on agricultural income in the long run. Our findings indicate a limited transfer efficiency of biofuel policy. We compare quantitative results with positions of farmers' associations.